A retrospective cohort study of PD-L1 prevalence, molecular associations and clinical outcomes in patients with NSCLC: Results from the European Thoracic Oncology Platform (ETOP) Lungscape Project. (May 2019) - Kerr, Keith M.; Thunnissen, Erik; Dafni, Urania; Finn, Stephen P.; Bubendorf, Lukas; Soltermann, Alex; Verbeken, Eric; Biernat, Wojciech; Warth, Arne; Marchetti, Antonio; Speel, Ernst-Jan M.; Pokharel, Sarawati; et al.
Highlights: A cohort study of surgically resected, stage I-III NSCLC cases from 15 centers. PD-L1 expression was assessed in 2182 NSCLC cases. PD-L1 positivity is associated with a better prognosis for adenocarcinoma patients. Abstract: Introduction: The PD-L1 biomarker is an important factor in selecting patients with non-small cell lung cancer for immunotherapy. While several reports suggest that PD-L1 positivity is linked to a poor prognosis, others suggest that PD-L1 positive status portends a good prognosis. Methods: PD-L1 positivity prevalence, assessed via immunohistochemistry (IHC) on tissue microarrays (TMAs), and its association with clinicopathological characteristics, molecular profiles and patient outcome- Relapse-free Survival (RFS), Time-to-Relapse (TTR) and Overall Survival (OS)- is explored in the ETOP Lungscape cohort of stage I-III non-small cell lung cancer (NSCLC). Tumors are considered positive if they have ≥1/5/25/50% neoplastic cell membrane staining. Results: PD-L1 expression was assessed in 2182 NSCLC cases (2008 evaluable, median follow-up 4.8 years, 54.6% still alive), from 15 ETOP centers. Adenocarcinomas represent 50.9% of the cohort (squamous cell: 42.4%). Former smokers are 53.7% (current: 31.6%, never: 10.5%). PD-L1 positivity prevalence is present in more than one third of the Lungscape cohort (1%/5% cut-offs). It doesn't differ between adenocarcinomas and squamous cell histologies, but is more frequently detected in higher stages, never smokers, larger tumors (1/5/25% cut-offs). With ≥1% cut-off it is significantly associated with IHC MET overexpression, expression of PTEN, EGFR and KRAS mutation (only for adenocarcinoma). Results for 5%, 25% and 50% cut-offs were similar, with MET being significantly associated with PD-L1 positivity both for AC (p < 0.001, 5%/25%/50% cut-offs) and SCC (p < 0.001, 5% & 50% cut-offs and p = 0.0017 for 25%). When adjusting for clinicopathological characteristics, a significant prognostic effect was identified in adenocarcinomas (adjusted p-values: 0.024/0.064/0.063 for RFS/TTR/OS 1% cut-off, analogous for 5%/25%, but not for 50%). Similar results obtained for the model including all histologies, but no effect was found for the squamous cell carcinomas. Conclusion: PD-L1 positivity, when adjusted for clinicopathological characteristics, is associated with a better prognosis for non-metastatic adenocarcinoma patients.